(untitled) (Fiep Bulletin - online, 2011)
The present study has as objective, to investigate the pupils of average and basic education during the lessons of physical education. The applied content was adapted games, as a pedagogical alternative. The project was developed in the Public/State College Prof Murilo Braga, situated in the Baixada Fluminense, state of Rio de Janeiro during March and April of the school year of 2009. To the most common school sports developed in the school, there were added games adapted to disabled children such as soccer and races for blind people, athletics, table tennis and volleyball for wheelchairs users. Besides trying these types of sports, the pupils also felt the difficulty of the disabled ones and empathized with other people who live with these conditions. An applied, descriptive and explaining research was conducted. The sources of data had been collected from fieldwork and literature research. The collected data had been collected from quantitative research and literature review.